CAFFEINE – A POPULAR STIMULANT AS A CAUSE OF INSOMNIA AMONG MEDICAL STUDENTS – A REVIEW OF THE LATEST LITERATURE - Emilia Majewska; Izabela Domańska; Aleksandra Sagan; Monika Domagała; Joanna Wiewióra; Weronika Duda; Małgorzata Piśkiewicz; Kamil Biedka; Jakub Bulski (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective Caffeine is a common stimulant frequently used by young people, particularly medical students. Despite its numerous beneficial properties, it also causes various adverse effects, including addiction. The aim of this study is to examine the relationship between insomnia among medical students and their caffeine consumption. Materials and Methods This review paper uses resources available in the Google Scholar databases. All the studies included in the review were published in 2024. The phrase "caffeine insomnia medical student" was used to search for relevant studies. These articles are available online and free-full text. Results Many medical students regularly consume caffeinated drinks. The reasons of using include combating fatigue, improving cognitive functions and concentration. However, its consumption is associated with negative health effects such as insomnia. Results of studies included in this review show that sleep disorders were reported by approximately 30% to nearly 50% of surveyed medical students consuming caffeinated drinks. Medical students suffering from insomnia showed worse test results. Sleep plays a crucial role in memory retention and information processing. Most of them lacked sufficient knowledge about the side effects of caffeine and the determination of a safe daily dose. Conclusions Insomnia is a common health issue among medical students. Regular caffeine consumption increases the risk of its occurrence. The surveyed students have limited knowledge about the side effects associated with caffeine use. To raise awareness among future doctors about the serious health consequences of excessive caffeine consumption, appropriate health education should be introduced during medical studies.